Existence of Noninner Automorphisms of Order-p in Some Finite p-Groups - Shivani (My University, 2017)
A long standing conjecture [10, Problem 4.13] asserts that every finite non- abelian p-group has a noninner automorphism of order p. The work pre- sented in this dissertation has been divided into three chapters. The first chapter is introductory. In chapter II, apart from setting up the notations and terminology to be used in sequel, we have presented some known results inter-related to our result. In chapter III, we studied the main results of Attar[14].
Master of Science -Mathematics & Computing
Keywords: Finite p-groups; Automorphism; Nilopotency; Frattini; Cyclic Group